Development of Science Learning Modules Based on Project Based Leraning on Additives and Addictive Substances (A Research in Class VIII SMP Negeri 7 Telaga Biru) - Alpinawati N. Masaguni; Chairunnisah J. Lamangantjo; Nancy Katili; Masrid Pikoli; Trisnawaty Junus Buhungo; Citron S. Payu (Postgraduate, University of Mataram, 2023)
This research is a development research (Research and Development) which aims to determine the validity, practicality and effectiveness of developing a Project Based Learning (PjBL) science learning module on additives and addictive substances. This research uses the ADDIE model up to the stage (Analysis, Design, Development, Implementation and Evaluation) and was tested in class VIII SMP Negeri 7 Telaga Biru with a one group pre test-post test design. The results showed that: (1) The developed module obtained an average of 3.66 with a valid category obtained through the validity test; (2) The developed module is practical as indicated by the learning is very well implemented with an average percentage of 92% and students state that the learning process using the Project Based Learning-based Science learning module is practical to be applied in the classroom; (3) The developed module is effective as indicated by students who are active in learning for three meetings with an average percentage of 85% (good category), the increase in student learning outcomes for the cognitive domain reaches an N-gain value of 0.71 including in the high category. Based on the results of this study, it can be concluded that the learning module developed is of high quality.